2022
DOI: 10.1155/2022/8223336
|View full text |Cite|
|
Sign up to set email alerts
|

To Systematically Evaluate and Analyze the Efficacy and Safety of Transcatheter Arterial Chemoembolization (TACE) in the Treatment of Primary Liver Cancer

Abstract: The efficacy and safety of transcatheter arterial chemoembolization (TACE) are systematically evaluated in the treatment of primary liver cancer, which provides a reference for clinical practice and more in-depth research. Cochrane Library, PubMed, EMbase, CBM, CNKI, VIP, and WanFang Data, supplemented by other searches, collected all randomized controlled trials (RCT) comparing TACE combined with TACE alone for HCC. The meta-analysis, after selecting the literature, extracting data, and evaluating the methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, patients with uHCC treated with TACE alone suffered high possibility of tumor recurrence and metastasis, which induces short survival. Also, repeated TACE treatment seriously damages liver function and increases the risk of liver failure ( 17 ). TACE embolizes the liver blood supply, leading to hypoxis tumor microenvironment, releasing a large number of cytokines that promotes revascularization of the residual tumor tissue ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with uHCC treated with TACE alone suffered high possibility of tumor recurrence and metastasis, which induces short survival. Also, repeated TACE treatment seriously damages liver function and increases the risk of liver failure ( 17 ). TACE embolizes the liver blood supply, leading to hypoxis tumor microenvironment, releasing a large number of cytokines that promotes revascularization of the residual tumor tissue ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“… 140 As a result, tumor therapy has gradually shifted towards multimodal approaches with flexible and adjustable advantages. Numerous studies have demonstrated that compared to single treatment strategies, combining multiple therapies offers distinct advantages in clinical cancer treatment, including efficient synergistic effects, 141 reduced adverse reactions, 142 and addressing drug resistance. 143 In recent years, the development of nano-drug delivery technology has provided a versatile platform for co-loading two or more drugs, opening up promising possibilities for combined tumor therapy.…”
Section: Combined Treatment Scheme Based On Ferroptosismentioning
confidence: 99%
“…As for the MWA method, the lesion can be accurately ablated under the guidance of CT, which is less likely to damage adjacent organs and tissues. However, this method requires a high level of skill, and there is a major risk of liver surface lesion bleeding, so relevant hemostatic measures need to be taken [2,3] . Relevant studies have suggested that these two treatments complement each other when used together.…”
Section: Introductionmentioning
confidence: 99%